Implementasi Kebijakan Kurikulum dalam Peningkatan Mutu Lulusan di MIN se-Kota Sibolga - Muhammad Rifai Harahap; Mhd. Syahdan Lubis; Syafaruddin Syafaruddin; Makmur Syukri (Al-Fikru: Jurnal Ilmiah, 2022)
This study aims to analyze (1) the implementation of the curriculum in improving the quality of graduates, (2) the strategy of teacher development in implementing the curriculum in improving the quality of graduates, and (3) the factors supporting and inhibiting the implementation of the curriculum in improving the quality of graduates. This research was conducted in MIN in Sibolga City using a qualitative research method with a descriptive study approach. Data collection techniques used are observation, interviews, and documentation studies. Data analysis used the Miles and Huberman technique, which included data collection, data reduction, and data conclusions. The results of the study indicate that implementation is realized through the management cycle, namely planning, organizing, implementing, monitoring and evaluating. The focus of the cycle is on improving the quality of graduates. Then to achieve this, teacher training is carried out through workshops, which practically there is no difference in MIN-se in Sibolga City. The coaching is divided into two, namely central coaching, namely from the Ministry of Education and Culture and the Ministry of Religion, and independent coaching, which is carried out at the discretion of the madrasa head by inviting experts. Supporting factors are the appropriate qualifications and competencies of teachers, as well as the teacher's motivation to make the program a success. Meanwhile, the inhibiting factors are that the facilities and infrastructure have not been maximally, and the real conditions in the field are often at odds with the ideal conditions expected by the government.